A millennium of climatic and floristic dynamics in the Eastern Cordillera of the Colombian Andes. (25th March 2022) - Correa‐Metrio, Alex; Escobar, Jaime; Bird, Broxton W.; Caballero‐Rodríguez, Dayenari; Steinman, Byron A.; Rodríguez‐Zorro, Paula A.; Curtis, Jason
Abstract: Aim: The transition from the Medieval Climate Anomaly (MCA, 950–1250 CE) to the Little Ice Age (LIA, 1350–1800 CE) is the largest pre‐industrial climate shift within the last two millennia, offering an opportunity to study how vegetation responds to rapid climate change. We analysed a sedimentary record from the Colombian Andes to reconstruct regional vegetation dynamics during this time interval, identify the modern environmental distribution of taxa present in the fossil record and provide a reference for modern regional temperature change. Location: Lake Tota, Eastern Cordillera, Colombian Andes. Taxon: Angiosperm and Gymnosperms. Methods: A sediment core was analysed for organic geochemistry and pollen to reconstruct environmental and vegetation variability between 800 and 1800 CE. Modern occurrences of individuals of the genera found in the fossil record were used to model the distribution of taxa across gradients of mean annual temperature and precipitation. These models were used to reconstruct temperature and precipitation across time and evaluate the probability of occurrence of taxa from the fossil record across the contemporary landscape. Results: Reconstructed regional vegetation dynamics were highly coupled with global temperature patterns. Reconstructed climate showed that conditions were warm and dry during the MCA, and cold and relatively wet during the LIA, although quantitative estimations might have been amplified by human disturbances. Rates of temperature change during the MCA‐LIA transition were substantially lower than those calculated for the last two decades. Vegetation turnover between 800 and 1800 CE resembled those expressed through a transect extending 30 km southeast from the lake. Main conclusions: Around lake Tota, modern rates of temperature change have no precedent within the last two millennia. The modern environmental affinities of taxa involved in vegetation turnover during the MCA‐LIA transition point to the importance of landscape diversity and connectivity for rapid vegetation response to climate change.